Negative experiences and out-group trust: The formation of natives' trust toward immigrants. (July 2017) - Freitag, Markus; Kijewski, Sara
Abstract: The steady flow of immigrants from all over the world challenges the social cohesion of states in a variety of ways. Against this backdrop, we extend previous research on attitudes toward immigrants by evaluating the formation of trust toward this group. Using a representative sample of the Swiss population, our results indicate that the violation of trust by negative experiences in the workplace is associated with lower levels of trust toward immigrants accordingly. However, we show that the relationship between negative experiences and trust toward immigrants is more powerful among those individuals who place high levels of trust in their own national group than for individuals who do not even trust their fellow group members.